Thirty-year land cover dynamics of a Ukrainian small town - Zibtseva Olha; Myroniuk Viktor; Yukhnovskyi Vasyl; Kirca Simay; Minder Victoria; Mishchenko Ihor; Pokotylova Kamila (Metsanduslikud Uurimused)
The purpose of the work was to determine trends in land cover dynamics in a case study of a small town for the period from 1991 to 2021 using GIS technologies to find measures to prevent negative anthropogenic impacts. The object of the study is the territory of the small town of Kaharlyk, Kyiv region, Ukraine, and its landscaping system. Dynamic processes in the town were monitored using freely available Landsat time series. The land cover was classified into five categories: forest, grassland, cropland, urban (buildings) and wetland (water). Using the Morphological Spatial Pattern Analysis, the dynamics of connectivity of elements of the urban forest was determined. Despite the relatively high rates of provision of the population with green infrastructure and a large forested area, the urban forests have an insular (fragmentary) nature and low connectivity. This does not contribute to the creation of a cohesive network and ecological framework of the town. It was established that there were no significant changes in the land cover of the town, however, some negative trends emerged, which should be taken into account in future urban planning.